Preparation And Characterization Of Microporous Activated Carbon From Oil Palm Shell By Physical Activation Using Purified Nitrogen - Allwar Allwar; Ahmad Md Noor; Moh Asri Moh Nawi (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
Oil palm shell, a byproduct of palm oil industry was successfully used as a raw material for the production of highly porous activated carbons. Preparation of activated carbon was carried out by physical activation under nitrogen at various activation temperatures. The nitrogen isotherms show Type I characteristics of microporous activated carbon. The maximum surface areas obtained at 900oC was 936 m2g-1. The morphology structure of the activated carbon indicated the existence of the porosities with different size pores. Keywords: Oil palm shell; Micropores; Physical activation; Nitrogen adsorption-desorption isotherm